Non-surgical endodontic treatment of a type III dens invaginatus with large perirradicular radiolucency using bioceramic materials: Case report (Research, Society and Development, 2024)
Dens invaginatus (DI), also known as dens in dente, is an uncommon dental anomaly in humans, characterized by irregular morphological development during odontogenesis, which can manifest in various coronal and radicular anatomies. Endodontic treatment of teeth with this variation demands anatomical knowledge, detailed planning, and the use of specialized techniques and materials. The objective of this research is to detail, through a case report, the non-surgical endodontic treatment of type III dens invaginatus in the upper lateral incisor with extensive periapical lesion, using bioceramic materials. An 18-year-old female patient was referred to the referral center by an orthodontist after radiographic examination revealed an extensive periapical lesion on tooth 12. Consequently, cone beam computed tomography was requested to assess the lesion and internal/external anatomy. The endodontic treatment was performed entirely under operative microscopy, utilizing mechanized instrumentation and thermoplasticized obturation. Disinfection was enhanced through activated irrigation technique and intracanal placement of bioceramic medication, with periapical repair achieved using bioceramic sealer cement. Long-term follow-up demonstrated that conservative endodontic treatment, employing modern techniques alongside bioceramic materials, proved effective in resolving complex cases.